Review Kuat Tekan Beton Polos dari Perspektif Mekanika Fraktur - Danang Murdiyanto; Benedictus Sonny Yoedono; Agnes Hanna Patty (Universitas Tribhuwana Tunggadewi Malang, 2018)
Concrete is a discreet material that consist of aggregate as filler and cement paste (matrix) as binder. Both of them work together as a composite or monolithic mechanism, depends on the interface zone characteristic that developed by aggregate. Monolithic mechanism leading to failure catastrophically (brittle and instantly), while composite mechanism prevails failure occurs gradually. Monolithic mechanism maybe found in high strength concrete where hardness and stiffness of aggregate are compatible with their matrix. At the moment when the matrix tensile strength (ft) is reached. The cracks will propagate quickly cutting both aggregates and matrix, as well at once. Contrary to the composite condition, when the matrix tensile strength is reached, the aggregate will take over the load and the crack will propagate through the interface zone. The perspective of fracture mechanics and the failure parameters explain the mechanism of crack propagation based on the energy principles. This investigation reviews the phenomenon of concrete compressive strength with angular aggregates compared to rounded aggregates on cylindrical specimens with diameter (d) 15 cm and height (h) 30 cm of the same compressive strength. The difference between them, shows the tendency of the influence of the interface zone as traction, which significantly contributes to the performance capacity before collapse